N-Amidation of Nitrogen-Containing Heterocyclic Compounds: Can We Apply Enzymatic Tools? - Anran Yang; Xue Miao; Liu Yang; Chao Xu; Wei Liu; Mo Xian; Huibin Zou (Bioengineering, 2023)
Amide bond is often seen in value-added nitrogen-containing heterocyclic compounds, which can present promising chemical, biological, and pharmaceutical significance. However, current synthesis methods in the preparation of amide-containing N-heterocyclic compounds have low specificity (large amount of by-products) and efficiency. In this study, we focused on reviewing the feasible enzymes (nitrogen acetyltransferase, carboxylic acid reductase, lipase, and cutinase) for the amidation of N-heterocyclic compounds; summarizing their advantages and weakness in the specific applications; and further predicting candidate enzymes through in silico structure-functional analysis. For future prospects, current enzymes demand further engineering and improving for practical industrial applications and more enzymatic tools need to be explored and developed for a broader range of N-heterocyclic substrates.